Design and Development of a Compact Drilling Machine for Small-scale Industries - Azhar, Muhammad Azreen Syafeezy; Mohd Yunos, Siti Nur Mariani (Research Progress in Mechanical and Manufacturing Engineering, 2024)
In the contemporary engineering landscape, drilling machines are pivotal in manufacturing, facilitating material processing and part fabrication. Despite their efficiency, conventional drilling machines exhibit significant drawbacks, primarily due to their large size, leading to high costs, and logistical challenges. This thesis project is carried out to design and fabricate a prototype of a smaller version of Bench Press Drilling Machine for small Industry mainly focused for small workshops. Using an Ishikawa diagram and root cause analysis, the primary issues associated with current drilling machines were identified. A morphological chart was then developed to enumerate possible solutions for each criterion, leading to the generation and evaluation of four concept designs to determine the optimal mechanism. The final design was modeled using SolidWorks, and a prototype was constructed and tested by experienced industrial workers to assess its reliability and efficiency. The study highlights the strengths and weaknesses of the miniature drilling machine compared to conventional models and proposes recommendations for further improvements to enhance the machine’s performance and efficiency.